Experimental Tapping of Sterculia villosa Roxb. for Gum Karaya - Verma, V. P. S.; Kharakwal, G. N. (Indian Forester, 1977)
The paper describes the details of the gum tapping experiments on Stereulia villosa Roxb. in Mohand Range of Siwalik Forest Division, Uttar Pradesh. The yield of sum from the healed surface, and untapped surface has been studied and it has been observed that there is no significant difference in the yield of gum from the healed surface and fresh surface at 5% probability.